2021
DOI: 10.17712/nsj.2021.1.20200089
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum uric acid in patients with traumatic brain injury or after cerebral tumor surgery

Abstract: Objectives: To investigate changes in sUA in patients with TBI or patients after cerebral tumor surgery and the possible mechanism of these changes. Methods: This prospective cohort study enrolled patients with TBI or underwent cerebral tumorOriginal Articles surgery at West China Hospital, China, from November 2014 to May 2018. Serum UA )sUA( levels, urine excretion, UA oxidant product allantoin and other clinical parameters were assessed.Results: 100 patients were enrolled for analysis. sUA in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A previous report suggested that inflammation in multiple sclerosis patients can induce hypouricemia through the overconsumption of UA as a scavenger of excessive oxidative stress PLOS ONE [30]. UA levels have also been reported to decline in patients with traumatic brain injury or after cerebral tumor surgery [31]. However, there has been no clear evidence that elucidates the mechanism underlying the effects of ischemic injury on UA levels, such as from studies that clarify the activities of xanthine oxidase and urate transporters using an animal stroke model.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report suggested that inflammation in multiple sclerosis patients can induce hypouricemia through the overconsumption of UA as a scavenger of excessive oxidative stress PLOS ONE [30]. UA levels have also been reported to decline in patients with traumatic brain injury or after cerebral tumor surgery [31]. However, there has been no clear evidence that elucidates the mechanism underlying the effects of ischemic injury on UA levels, such as from studies that clarify the activities of xanthine oxidase and urate transporters using an animal stroke model.…”
Section: Discussionmentioning
confidence: 99%